PENGARUH TINGKAT BUNGA PASAR, KUPON DAN WAKTU JATUH TEMPO OBLIGASI TERHADAP HARGA OBLIGASI PERINGKAT AAA DAN PERINGKAT BBB DI BURSA EFEK INDONESIA - I Gusti Ngurah Satria Wijaya; Putu Pande Yudiastra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Research on bonds is still limited compared to research on stocks in Indonesia. Bonds can be one type of asset that is quite interesting, because the bond is able to provide fixed income for investors who do not like the risk and can be used as an alternative investment in addition to stocks. This study aims to determine the effect of market interest rate, coupon and bond maturity to the price change of AAA rating bonds and BBB rating in Indonesia Stock Exchange. The population in this study are all listed corporate bonds traded in Indonesia Stock Exchange (BEI) from 2012 until 2015. Testing research hypothesis used multiple linear regression analysis techniques. The result of this study is that market interest significantly negatively affect the price change of AAA rating bond and BBB rating, coupon rate significantly positively affect the price change of AAA rating bond and BBB rating, and maturity time significantly negatively affectthe price change of AAA rating bond and BBB rating in Indonesia Stock Exchange.